ACUTE DISSEMINATED ENCEPHALOMYELITIS FOLLOWING A DIPHTHERIA-PERTUSSIS-TETANUS VACCINATION: A CASE REPORT - Stephanie Angela Prijanto; Tikto Wahyono; Pipit Soesilowati (JURNAL WIDYA MEDIKA, 2022)
Introduction: Acute disseminated encephalomyelitis (ADEM) is a rare, acute progressive autoimmune disease that occurs in the brain and spinal cord, in response to infection or immunization. Myelin autoantigens could share similar antigenic determinants with a pathogen and cross-react with a human’s antibody, causing demyelination of the nerve sheath. Identifying ADEM is essential to treat the patient and reduce any sequelae. Case description: An 11-year-old male was brought to the ER with one day of weakness of the face and the left side of the body. Along with that, the patient vomited, complained of headache and fever. One day prior, the patient received a Diphtheria-Pertussis-Tetanus Vaccination at his elementary school. A head computer tomography (CT) scan with contrast was done and showed multiple hypodense lesions in the bilateral internal capsule, bilateral lateral periventricular, subcortex of the right frontal lobe, and right cerebellum, with suspicion of ADEM. Discussion: There were many clinical signs of patients with ADEM, depending on the lesion. Brain and cerebellar lesions can cause irritability, confusion, coma, incoordination, and gait problems. Spine lesions can cause numbness and paralysis of the limbs. Lesions in the cranial nerve can cause dysarthria, blurry vision, double vision, and facial weakness. Conclusion: The prognosis for ADEM is good and often has improvement within a month. However, some patients need to undergo supportive therapy as appropriate. Further follow-up needs to be done to evaluate the disease progression, as ADEM may be manifesting as Multiphasic ADEM or any other demyelinating disease.